2013
DOI: 10.1371/journal.pone.0053989
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin1 (STC1) Inhibits Cell Proliferation and Invasion of Cervical Cancer Cells

Abstract: STC1 is a glycoprotein hormone involved in calcium/phosphate (Pi) homeostasis. There is mounting evidence that STC1 is tightly associated with the development of cancer. But the function of STC1 in cancer is not fully understood. Here, we found that STC1 is down-regulated in Clinical tissues of cervical cancer compared to the adjacent normal cervical tissues (15 cases). Subsequently, the expression of STC1 was knocked down by RNA interference in cervical cancer CaSki cells and the low expression promoted cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 28 publications
6
37
0
Order By: Relevance
“…In agreement with our tissue findings, STC1 was found to be highly expressed in ccRCC cell lines, with the greatest levels of STC1 expression being observed in metastatic cell lines. These data are consistent with observations reported for the majority of malignancies [ 10 , 22 , 23 , 46 , 47 ], although with the exception of cervical cancer [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our tissue findings, STC1 was found to be highly expressed in ccRCC cell lines, with the greatest levels of STC1 expression being observed in metastatic cell lines. These data are consistent with observations reported for the majority of malignancies [ 10 , 22 , 23 , 46 , 47 ], although with the exception of cervical cancer [ 48 ].…”
Section: Discussionsupporting
confidence: 93%
“…5C and data not shown). Furthermore, although both wild-type and mutant JMJD3 exhibited similar binding to a previously identified NF-kB p65-binding site at the STC1 promoter (38), H3K27 trimethylation at this location was significantly decreased only in JMJD3wt cells (Fig. 5D).…”
Section: Stc1 a Novel Target Of Jmjd3 Confers Self-renewal Ability supporting
confidence: 52%
“…STC-1 is involved with various biological events such as cell proliferation, migration, invasion, apoptosis, and inflammation in colon, gastric, and cervical cancer (14,16,31,32). In a recent study, we reported that the motility of TNBC cells such as invasion and migration was higher than these abilities in non-TNBC cells through TGF-β1 and -β2 expression (33).…”
Section: Discussionmentioning
confidence: 99%